Initial Flowering and Fruiting of Neem - National Provenence Trial - Gupta, P. K.; Pal, R. S.; Emmanuel, C. J. S. K. (Indian Forester, 1995)
Studies on fruiting in neem in the 3 year old provenance trial raised at AFRI, Jodhpur, was carried out during June 1995. Analysis of recorded data indicate that 206 trees (25.52%) of plants exhibited fruiting in the third year with variations depending on different provenances; 30 plants (3.72%) exhihited flowering at the time when the other trees were fruiting. In 2 plants (0.25%), flowering and matured fruits were observed occurring at the same time. One plus tree with respect to the extent of fruiting was identified from the Kanpur provenances, Tree No. 46.